Simbolisme dalam tradisi lisan Pasang Ri Kajang: Tinjauan semiotik - Gising, Basrah (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
Semiotics is a set of analytical approaches that has been applied in linguistics and anthropology. This article focuses on language and cultural symbols expressed in Pasang ri Kajang and analyzes them based on the grand theory of semantics. This research adopts a qualitative research perspective. Data validity was ensured through data collection methods including interviews, recordings, note-taking, elicitation, and focus group discussions. The results indicate that Pasang ri Kajang contains sacred ancestral messages transmitted through oral tradition. These messages embody forms of local wisdom related to sustainable environmental management. The focus of this research is the local knowledge system concerning the hydraulic cycle, as expressed in various elements of Pasang ri Kajang. The relationships among these elements construct a substantial concept related to the hydraulic cycle within an ecological framework.